UNLOCKING FIRM VALUE THROUGH CORPORATE GOVERNANCE : EMPIRICAL EVIDENCE FROM INDONESIA’S BASIC MATERIAL INDUSTRY - Munawarah Munawarah; Gracelely A. Situmorang; May Hana Bilqis Rangkuti (UNIVERSITAS DHARMAWANGSA, 2026)
This study aims to analyze the effect of corporate governance implementation on firm value in the basic materials sector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023. The independent variables include institutional ownership (IO), board of directors diligence (BDD), independent commissioners (IC), and audit committees(AC). The dependent variable, firm value, is measured using the Tobin’s Q ratio. This study employs a quantitative approach with multiple linear regression analysis. The sample was selected purposively, comprising 61 companies over 4 years of observation, yielding 244 data points. The results show that audit committees have a positive and significant effect. In contrast, institutional ownership, board of directors diligence, and independent commissioners do not have a significant effect on firm value.